Advances in the design of self-supported ion-conducting membranes-new family of columnar liquid crystalline polyamines. Part 1: Copolymer synthesis and membrane preparation. (22nd November 2016) - Montané, Xavier; Bogdanowicz, Krzysztof Artur; Colace, Gianmarco; Reina, José Antonio; Cerruti, Pierfrancesco; Lederer, Albena; Giamberini, Marta
Abstract: Poly[2-(aziridin-1-yl)ethanol] (PAZE) is a suitable polyamine candidate which can be dendronised with 3, 4, 5-tris[4-(n-dodecan-1-yloxy)benzyloxy]benzoic acid (TAP) in order to obtain liquid crystalline columnar polyamines, as previously reported. However, the resulting copolymers evidenced a strong tendency to crystallise which leads to the detriment of columnar phase stability and the mechanical properties of the resulting polymeric membranes. In order to overcome this drawback, we successfully prepared LC columnar polyamines based on poly[2-(aziridin-1-yl)ethanol] modified with both TAP and benzoyl chloride at different extents. The presence of the dendron group induces self-assembling into a columnar structure, due to an exo-recognition of the side-chain dendrons, while the benzoyl group is expected to inhibit polymer crystallinity. All copolymers, except one, have lower melting points and exhibit higher clearing temperatures (Tc ), when compared to the LC polyamines obtained by modification of PAZE with TAP only, reported in previous studies. In all cases they exhibited LC columnar mesophases after annealing, as inferred by DSC, XRD and POM. When casted as membranes, these columnar copolyamines can be homeotropically oriented under thermal treatment at optimal conditions, as was confirmed by X-ray diffraction studies at low 2θ angles. Additionally, SEM microscopy was used in order to evaluate the morphology of the prepared membranes. Graphical abstract: Highlights: Poly[2-(aziridin-1-yl)ethanol] was modified with benzoyl chloride and TAP dendron. Obtained copolymers showed liquid crystalline behaviour. Under thermal treatment, these copolymers self-assemble into a columnar structure. Oriented membranes could be successfully prepared out of selected copolymers.